Lithium metal composite oxide, positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
By optimizing the void structure and composition of lithium metal composite oxide, the first discharge capacity and rate characteristics of lithium secondary batteries are improved, and the improvement space for lithium secondary batteries in the prior art is solved.
Patent Information
- Application Number
- CN202380089273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-12-01
- Publication Date
- 2025-08-05
AI Technical Summary
There is room for improvement in the first discharge capacity and rate characteristics of existing lithium secondary batteries.
A lithium metal composite oxide with a specific void structure is adopted, and the secondary particles have a void of more than 0.2 μm inside the secondary particles, the weighted average value of the aspect ratio area is 1.8 or more and 5.0 or less, and the proportion of secondary particles in the internal void is 3% or more and 95% or less, so as to optimize the composition and structure of the lithium metal composite oxide.
The first discharge capacity and rate characteristics of lithium secondary batteries are improved, and the stability and energy density of lithium metal composite oxides are enhanced.
Smart Images

Figure CN120435443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium metal composite oxide, a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery.
[0002] This application claims priority based on Japanese Patent Application No. 2022-193520 filed in Japan on December 2, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Lithium metal composite oxides are used as positive electrode active materials for lithium secondary batteries. With the goal of improving the performance of lithium secondary batteries, research has been conducted on the composition, physical properties, pore structure, etc. of lithium metal composite oxides.
[0004] For example, Patent Document 1 investigates the pore structure of lithium metal composite oxides. Specifically, the disclosure discloses a positive electrode active material comprising secondary particles having a shell formed from primary particles and a hollow portion formed within the shell. The shell comprises through-holes connecting the outer portion of the shell with the hollow portion. The disclosure discloses that by setting the diameter of the through-holes and the pore distribution of the through-holes within specific ranges, the output power of a lithium secondary battery can be increased.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: JP-A-2017-004635 Summary of the Invention
[0008] Problems to be solved by the invention
[0009] In the development of applications of lithium secondary batteries, further improvements in initial discharge capacity and rate characteristics are required for lithium secondary batteries.
[0010] The present invention is completed in view of the above situation, and the subject is to provide a lithium metal composite oxide that can obtain a lithium secondary battery with high first discharge capacity and rate characteristics, a positive electrode active material for a lithium secondary battery containing the above lithium metal composite oxide, and a positive electrode for a lithium secondary battery and a lithium secondary battery containing the above positive electrode active material for a lithium secondary battery.
[0011] Means for solving problems
[0012] The present invention is as follows [1] to
[12] .
[0013] [1] A lithium metal composite oxide comprising a plurality of secondary particles, wherein the secondary particles are aggregates of primary particles, at least a portion of the secondary particles having voids therein, wherein the contour of the voids exposed in the cross section of the secondary particles having the voids therein is such that the area-weighted average of the aspect ratios of the voids having an equivalent circle diameter of 0.2 μm or greater is 1.8 or greater and 5.0 or less, and the number of secondary particles having voids having an equivalent circle diameter of 0.5 μm or greater therein is 3% or greater and 95% or less relative to the total number of the secondary particles.
[0014] [2] The lithium metal composite oxide according to [1], wherein the average value of the equivalent circle diameter of the voids having an equivalent circle diameter of 0.2 μm or more is 0.3 μm or more.
[0015] [3] The lithium metal composite oxide according to [1] or [2], wherein the area-weighted average of the major axes of the voids having an equivalent circle diameter of 0.2 μm or greater is 0.2 μm or greater and 15 μm or less.
[0016] [4] The lithium metal composite oxide according to any one of [1] to [3], wherein the area-weighted average of the aspect ratios of the secondary particles having voids with an equivalent circle diameter of 0.2 μm or greater inside is 1.0 or greater and 5.0 or less.
[0017] [5] The lithium metal composite oxide according to any one of [1] to [4], wherein the ratio of the area-weighted average value of the major diameter of the voids having an equivalent circle diameter of 0.2 μm or more to the area-weighted average value of the major diameter of the secondary particles having voids having an equivalent circle diameter of 0.2 μm or more therein is greater than 0.001 and less than 0.9.
[0018] [6] The lithium metal composite oxide according to any one of [1] to [5], wherein the 50% cumulative volume particle size (D 50 It is 5 μm or more and 20 μm or less.
[0019] [7] The lithium metal composite oxide according to any one of [1] to [6], which contains Li and Ni and may also contain at least one element selected from the group consisting of Co and Mn, and the ratio of the molar number of Co contained in the above lithium metal composite oxide to the total molar number of elements other than Li and oxygen is 5% or less.
[0020] [8] The lithium metal composite oxide according to any one of [1] to [7], which is represented by the following composition formula (I).
[0021] Li[Li x (Ni (1-y-z) M1y M2 z ) 1-x ]O2(I)
[0022] In the above composition formula (I), M1 represents one or more elements selected from the group consisting of Co, Mn and Al, M2 represents one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, B, Si, S and P, and the above composition formula (I) satisfies -0.1≤x≤0.2, 0<y<1, 0≤z≤0.2, and y+z<1.
[0023] [9] The lithium metal composite oxide according to any one of [1] to [8], wherein in a powder X-ray diffraction measurement using CuKα radiation, the peak area of the diffraction peak existing in the range of 2θ=18.5±1° is set as I D The peak area of the diffraction peak existing in the range of 2θ=44.5±1° is set as I E When I D / I E It is above 0.8.
[0024]
[10] A positive electrode active material for a lithium secondary battery, comprising the lithium metal composite oxide according to any one of [1] to [9].
[0025]
[11] A positive electrode for a lithium secondary battery, comprising the positive electrode active material for a lithium secondary battery according to
[10] .
[0026]
[12] A lithium secondary battery comprising the positive electrode for a lithium secondary battery according to
[11] .
[0027] Effects of the Invention
[0028] According to the present invention, a lithium metal composite oxide capable of obtaining a lithium secondary battery having high initial discharge capacity and rate characteristics, a positive electrode active material for a lithium secondary battery comprising the lithium metal composite oxide, and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of a cross-sectional image of secondary particles contained in a lithium metal composite oxide after binarization processing.
[0030] Figure 2 This is a diagram schematically showing the configuration of an example of a lithium secondary battery.
[0031] Figure 3 This is a schematic diagram showing an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION
[0032] The definitions of terms used in this specification are as follows.
[0033] The metal composite compound (Metal Composite Compound) is also referred to as "MCC" hereinafter.
[0034] Lithium metal composite oxide (Lithium Metal Composite Oxide) is hereinafter also referred to as "LiMO".
[0035] The cathode active material for lithium secondary batteries is hereinafter also referred to as “CAM”.
[0036] "Ni" does not represent nickel metal alone, but represents the Ni element. The same applies to other elements such as Co and Mn.
[0037] “Primary particles” refer to particles that appear to have no grain boundaries when observed at a 10,000-fold magnification using a scanning electron microscope (hereinafter also referred to as “SEM”).
[0038] "Secondary particles" refer to particles formed by aggregation of the above-mentioned primary particles. In other words, secondary particles are aggregates of primary particles.
[0039] When a numerical range is described as, for example, "5.00 to 15.00 μm", it means a range from 5.00 μm to 15.00 μm, and means a numerical range including 5.00 μm as a lower limit and 15.00 μm as an upper limit.
[0040] In the numerical ranges of this specification, the upper limit and the lower limit can be arbitrarily combined. The numerical ranges of various physical properties, compositions, and production conditions can be arbitrarily combined.
[0041] The equivalent circle diameter is the diameter of a circle when the area of the cross section is set to S and the area is (4×S / π). 1 / 2 The length of the representation.
[0042] The lithium secondary battery refers to a lithium ion secondary battery.
[0043] The measurement methods of various parameters of LiMO in this specification are as follows.
[0044] <Area-weighted average of aspect ratio of voids, etc.>
[0045] Acquisition of cross-sectional images of secondary particles contained in LiMO
[0046] LiMO is processed to obtain a cross section of LiMO. As an example of a method for obtaining a cross section of LiMO, a method of processing LiMO using a focused ion beam device can be cited as an example. Alternatively, a portion of a positive electrode produced using LiMO as a CAM can be cut out and processed using an ion milling device to obtain a cross section of LiMO contained in the positive electrode active material layer of the positive electrode.
[0047] As samples to be cross-sectioned, not only LiMO and positive electrodes but also samples obtained by reinforcing LiMO with resin can be suitably selected. Furthermore, as a method for preparing cross sections, not only ion beam methods but also milling can be suitably selected.
[0048] Using a SEM, a cross-section of the LiMO obtained by the above processing was observed using backscattered electron imaging to obtain a cross-sectional image of the secondary particles. Measurement conditions can be, for example, set to an accelerating voltage of 5 kV and an image resolution of x, y = 0.023 μm, z = 0.023 μm. Furthermore, the magnification should be set to a level that allows for the identification of 10 or more secondary particles within a single field of view.
[0049] Binarization of cross-sectional images of secondary particles contained in LiMO
[0050] The cross-sectional image of the secondary particles contained in LiMO is taken into a computer, and image analysis software is used to perform a binarization process with the intermediate value of the maximum brightness and the minimum brightness in the cross-sectional image of the secondary particles, so as to obtain a binary image in which the solid cross section of the above-mentioned secondary particles is set to an arbitrary color (e.g., gray) and the void (hereinafter referred to as the void cross section) exposed in the solid cross section of the above-mentioned secondary particles is set to an arbitrary color (e.g., white). As image analysis software, for example, quantitative analysis software (TRI / 3D-BON-FCS, Ratoc System Engineering) can be used. When using the quantitative analysis software, the function of the software, i.e., Auto-LW, can be used to perform a binarization process on the image. At this time, the cross-sectional image before the binarization process is visually inspected, and the cross-sectional images before and after the binarization process are compared to confirm that there is no inconsistency with the solid cross section and the void cross section of the secondary particles. When inconsistency is seen, the threshold value for binarization is adjusted. It should be noted that when LiMO contains Al, Al segregation is sometimes generated in the solid cross section and the void cross section of the secondary particles, showing an intermediate contrast. In such cases, the image processing function is used to extract only the middle contrast portion and overlap it with the void cross section. This process allows for more accurate discrimination between the solid cross section of the secondary particles and the void cross section, eliminating the effects of Al segregation, and for binarization.
[0051] From the binarized image, image calculation functions are used to remove secondary particles with an equivalent circle diameter of 6.0 μm or less. Furthermore, secondary particles that are only partially visible at the edges of the image, those that have broken apart during binarization, and those with unclear particle shapes are removed to produce a "binarized image." In other words, the secondary particles used for the calculation of parameters described later in this specification are only those with an equivalent circle diameter exceeding 6.0 μm.
[0052] Figure 1 This is a schematic diagram of a binarized image of secondary particles contained in LiMO. Figure 1 The cross section 40 of the secondary particle has a solid cross section 41 of the secondary particle, a solid cross section 42 of the secondary particle, a solid cross section 43 of the secondary particle, a void cross section 44, and a void cross section 45. The void cross section 44 is a void cross section with an equivalent circle diameter of 0.2 μm or more, and the void cross section 45 is a void cross section with an equivalent circle diameter of less than 0.2 μm. Figure 1 In the case of the equivalent circle diameter of the secondary particle, the equivalent circle diameter is calculated from the total area of the solid cross section 41 of the secondary particle, the solid cross section 42 of the secondary particle, the solid cross section 43 of the secondary particle, the void cross section 44 and the void cross section 45.
[0053] Since the pore cross section extracted from the binarized image also includes extremely small pores between primary particles, only the pores with an equivalent circle diameter of 0.2 μm or more (i.e., an area of 0.03 μm) are included. 2 The void cross sections (above) are extracted, and the aspect ratio and the like are calculated for these void cross sections. In the following, the void cross sections with an equivalent circle diameter of 0.2 μm or more are recorded as "void cross section A". In addition, the void cross sections with an equivalent circle diameter of 0.5 μm or more are recorded as "void cross section B". When calculating the equivalent circle diameter of the void cross section 44 or the void cross section 45, the equivalent circle diameter is calculated from the area of the void cross section 44 or the void cross section 45, respectively. That is, when calculating the equivalent circle diameter of the void cross section 44 or the void cross section 45, the areas of the solid cross section 41 of the secondary particle, the solid cross section 42 of the secondary particle, and the solid cross section 43 of the secondary particle are not taken into consideration.
[0054] In the following, voids having an equivalent circle diameter of 0.2 μm or more are referred to as "voids A," and secondary particles having voids A therein are referred to as "secondary particles A." Furthermore, voids having an equivalent circle diameter of 0.5 μm or more are referred to as "voids B," and secondary particles having voids B therein are referred to as "secondary particles B."
[0055] (Area-weighted average of the aspect ratio of gap A)
[0056] For the contour shape of the void cross section A in the obtained binarized image, the aspect ratio of the void A can be calculated by dividing the major diameter of the void cross section A by the minor diameter. It should be noted that the "major diameter" refers to the length of the major diameter of the circle with the longest diameter within the diameter of the circle circumscribed with the void cross section A (the diameter if the circle is a perfect circle, or twice the major radius if the circle is an ellipse), and the "minor diameter" refers to the length of the diameter within the diameter of the circle that is orthogonal to the major diameter and has the longest diameter (the diameter if the circle is a perfect circle, or twice the minor radius if the circle is an ellipse).
[0057] For the contour shapes of all void cross sections A confirmed in the binarized image, the aspect ratio and area of each void cross section A are measured, and the product of the aspect ratio and area is calculated for all void cross sections A. By dividing the total value of the product of the aspect ratio and area of each void cross section A by the total area of all void cross sections A, the "area-weighted average of the aspect ratios of voids A" can be calculated. For example, when void cross sections A' and void cross sections A" exist in the binarized image, the following formula A is used for calculation.
[0058] Area-weighted average of the aspect ratio of void A = (aspect ratio of void section A' × area of void section A' + aspect ratio of void section A" × area of void section A") / (area of void section A' + area of void section A") (Formula A)
[0059] (Average value of the equivalent circle diameter of gap A)
[0060] For the contour shapes of all the void cross sections A confirmed in the binarized image, the product of the equivalent circular diameter and the area of each void cross section A is calculated. By dividing the total value of the product of the equivalent circular diameter and the area of each void cross section A by the total area of all the void cross sections A, the "average value of the equivalent circular diameter of the void A" can be calculated. For example, when there are void cross sections A' and void cross sections A" in the binarized image, it is calculated using the following formula B.
[0061] Average value of the equivalent circular diameter of void A = (equivalent circular diameter of void section A' × area of void section A' + equivalent circular diameter of void section A" × area of void section A") / (area of void section A' + area of void section A") (Formula B)
[0062] (Area-weighted average of the major diameter and the minor diameter of the gap A)
[0063] For the contour shapes of all the void sections A confirmed in the binarized image, the major diameter, minor diameter and area of each void section A are measured, and the product of the major diameter and the area, and the product of the minor diameter and the area are calculated for all the void sections A. By dividing the total value of the product of the major diameter and the area of each void section A by the total area of all the void sections A, the "area-weighted average value of the major diameter of the void A" can be calculated. By dividing the total value of the product of the minor diameter and the area of each void section A by the total area of all the void sections A, the "area-weighted average value of the minor diameter of the void A" can be calculated. For example, when there are void sections A' and void sections A" in the binarized image, they are calculated using the following formulas C and D.
[0064] Area-weighted average of the major diameter of void A = (major diameter of void section A' × area of void section A' + major diameter of void section A" × area of void section A") / (area of void section A' + area of void section A") (Formula C)
[0065] Area-weighted average of the minor diameter of void A = (minor diameter of void section A' × area of void section A' + minor diameter of void section A" × area of void section A") / (area of void section A' + area of void section A") (Formula D)
[0066] (Average aspect ratio of voids B in one secondary particle)
[0067] When a secondary particle has only one void B, the aspect ratio of the void B in the void cross section B is the "average aspect ratio of voids B in one secondary particle." When a secondary particle has two or more voids B, the aspect ratios of all voids B are measured for the contour shape of the void cross sections B contained in one secondary particle, and the total of these values is divided by the total number of void cross sections B contained in one secondary particle to determine the "average aspect ratio of voids B in one secondary particle."
[0068] (Area-weighted average of the aspect ratios of secondary particles A)
[0069] All the secondary particle sections A (cross sections of secondary particles A) with the void cross sections A confirmed in the binarized image are extracted. For the contour shape of the extracted secondary particle sections A, the aspect ratio of the secondary particle A can be calculated by dividing the major diameter of the secondary particle section A by the minor diameter. It should be noted that "major diameter" refers to the length of the major diameter of the circle with the longest diameter within the diameter of the circle circumscribed with the secondary particle section A (the diameter when the circle is a perfect circle, and twice the major radius when the circle is an ellipse), and "minor diameter" refers to the length of the diameter within the diameter of the above-mentioned circle that is orthogonal to the above-mentioned major diameter and has the longest diameter (the diameter when the circle is a perfect circle, and twice the minor radius when the circle is an ellipse).
[0070] For the contour shapes of all the secondary particle cross sections A extracted above, the aspect ratio of each secondary particle cross section A is measured, and the product of the aspect ratio and the area of all the secondary particle cross sections A is calculated. By dividing the total value of the product of the aspect ratio and the area of each secondary particle cross section A by the total area of all the secondary particle cross sections A, the "area-weighted average of the aspect ratios of the secondary particles A" can be calculated. For example, when the secondary particle cross sections A' and the secondary particle cross section A" are extracted from the binarized image, it is calculated using the following formula E.
[0071] Area-weighted average of the aspect ratio of the secondary particle A = (aspect ratio of the secondary particle cross section A' × area of the secondary particle cross section A' + aspect ratio of the secondary particle cross section A" × area of the secondary particle cross section A") / (area of the secondary particle cross section A' + area of the secondary particle cross section A") (Formula E)
[0072] (Area-weighted average of the major diameter and the minor diameter of the secondary particles A)
[0073] For the contour shapes of all the secondary particle cross sections A extracted above, the major diameter, minor diameter and area of each secondary particle cross section A are measured, and the product of the major diameter and the area, and the product of the minor diameter and the area of all the secondary particle cross sections A are calculated. By dividing the total value of the product of the major diameter and the area of each secondary particle cross section A by the total area of all the secondary particle cross sections A, the "area weighted average value of the major diameter of the secondary particle A" can be calculated. By dividing the total value of the product of the minor diameter and the area of each secondary particle cross section A by the total area of all the secondary particle cross sections A, the "area weighted average value of the minor diameter of the secondary particle A" can be calculated. For example, when the secondary particle cross section A' and the secondary particle cross section A" are extracted from the binarized image, they are calculated using the following formulas F and G.
[0074] Area-weighted average of the major axis of secondary particle A = (major axis of secondary particle cross-section A' × area of secondary particle cross-section A' + major axis of secondary particle cross-section A'' × area of secondary particle cross-section A'') / (area of secondary particle cross-section A' + area of secondary particle cross-section A'') (Equation F)
[0075] Area-weighted average of the minor axis of secondary particle A = (minor axis of secondary particle cross-section A' × area of secondary particle cross-section A' + minor axis of secondary particle cross-section A'' × area of secondary particle cross-section A'') / (area of secondary particle cross-section A' + area of secondary particle cross-section A'') (Equation G)
[0076] <D 50 >
[0077] The 50% cumulative volume particle size of LiMO, i.e., D 50 (unit: μm) can be obtained from the particle size distribution of LiMO measured by the laser diffraction scattering method. Specifically, 0.10 g of the LiMO powder is put into 50 mL of a 0.20 mass% sodium hexametaphosphate aqueous solution to obtain a dispersion liquid in which the above powder is dispersed. Then, for the obtained dispersion liquid, a laser diffraction scattering particle size distribution measuring device (for example, manufactured by MicrotracBEL Co., Ltd., Microtrac MT3300EXII) is used to measure the particle size distribution, and a volume-based cumulative particle size distribution curve is obtained. In the obtained cumulative particle size distribution curve, the particle size value when 50% is accumulated from the side of the fine particles is D 50 .
[0078] <Composition>
[0079] The composition of each element of LiMO can be measured by inductively coupled plasma emission spectrometry (ICP). For example, after dissolving LiMO in hydrochloric acid, an inductively coupled plasma emission spectrometer (for example, manufactured by SIINanoTechnology Co., Ltd., SPS3000) can be used to measure the amount of each element.
[0080] <XRD Pattern>
[0081] The XRD pattern of LiMO can be obtained by powder X-ray diffraction measurement with CuKα set as the radiation source and the measurement range of the diffraction angle 2θ set to 10 - 90°. For example, for LiMO, an X-ray diffractometer (for example, manufactured by Rigaku Corporation, Ultima IV) can be used to obtain the XRD pattern. The obtained XRD pattern can be analyzed using analysis software (for example, manufactured by Rigaku Corporation, integrated powder X-ray analysis software PDXL2).
[0082] <Initial Discharge Capacity and Rate Characteristics>
[0083] The evaluation method of LiMO in this specification is as follows: A lithium secondary battery is produced using LiMO as CAM, and the initial discharge capacity and rate characteristics are measured.
[0084] (Manufacturing of positive electrodes for lithium secondary batteries)
[0085] A paste-like positive electrode mixture was prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) to a composition of CAM:conductive material:binder = 92:5:3 (mass ratio). N-methyl-2-pyrrolidone was used as the organic solvent during the preparation of the positive electrode mixture.
[0086] The obtained positive electrode mixture was applied to a 40 μm thick Al foil serving as a current collector and vacuum dried at 150°C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of the positive electrode for a lithium secondary battery was set to 1.65 cm 2 .
[0087] (Manufacturing of lithium secondary batteries)
[0088] The following operations were performed in a glove box under an argon atmosphere.
[0089] The lithium secondary battery positive electrode was placed face down on the lower cover of a coin-type R2032 battery (manufactured by Hohsen Co., Ltd.). A polypropylene porous membrane separator (25 μm thick) was placed on top. 300 μl of electrolyte was injected into the separator. The electrolyte used was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (30:35:35 by volume) with LiPF6 dissolved at a ratio of 1 mol / l.
[0090] Next, metallic lithium was used as a negative electrode and placed on the upper side of the separator. An upper cover was placed with a gasket interposed therebetween and caulking was performed with a caulking machine to produce a lithium secondary battery.
[0091] (First discharge capacity)
[0092] Using the produced lithium secondary battery, an initial discharge capacity test was carried out by the following method, and the initial discharge capacity was calculated.
[0093] First discharge capacity test
[0094] The lithium secondary battery was left to stand at 25° C. for 12 hours to allow the separator and the positive electrode mixture layer to be fully impregnated with the electrolyte.
[0095] Next, at a test temperature of 25°C, constant-current and constant-voltage charging and constant-current discharging were performed with a current setting of 0.20 CA for both charging and discharging. The maximum charging voltage was set to 4.30 V, and the minimum discharging voltage was set to 2.50 V. The charging time was set to 6 hours, and the discharging time was set to 5 hours. The discharge capacity was measured and the obtained value was used as the "initial discharge capacity" (mAh / g).
[0096] (Rate characteristics)
[0097] Using the produced lithium secondary battery, a discharge rate test was carried out by the following method, and the discharge capacity was calculated. The obtained value was defined as "rate characteristic" (mAh / g).
[0098] Discharge rate test
[0099] The discharge capacity when constant current discharge was performed under the following conditions was used as the rate characteristic.
[0100] Test temperature: 25℃
[0101] Maximum charging voltage 4.3V, charging current 1.00CA, constant current and constant voltage charging
[0102] Minimum discharge voltage 2.5V, discharge current 5.00CA, constant current discharge
[0103] Lithium Metal Composite Oxides
[0104] LiMO is an aggregate of multiple particles. In other words, LiMO is in powder form. LiMO has multiple secondary particles that are aggregates of primary particles. LiMO can also contain only secondary particles or a mixture of primary and secondary particles.
[0105] At least a portion of the secondary particles have voids therein, and with respect to the contour shape of the voids exposed in a cross-section of the secondary particles having the voids therein, an area-weighted average of the aspect ratios of the voids A is 1.8 to 5.0. The number of the secondary particles B having the voids B therein relative to the total number of the secondary particles is 3 to 95%.
[0106] The area-weighted average value of the aspect ratio of the voids A is preferably 1.9 or greater, more preferably 2.0 or greater. The area-weighted average value of the aspect ratio of the voids A is preferably 4.0 or less, more preferably 3.5 or less. Examples of the area-weighted average value of the aspect ratio of the voids A include 1.9 to 4.0, and 2.0 to 3.5.
[0107] Since at least some of the plurality of secondary particles contained in LiMO have voids inside, expansion and contraction of LiMO caused by lithium ion insertion and removal during charge and lithium ion insertion during discharge are mitigated, thereby stabilizing the crystal structure of LiMO.
[0108] In addition, the area-weighted average of the aspect ratio of the gap A being above the above lower limit means that the gap cross section is relatively flat. By having a flat gap cross section, the secondary particles deform in the width direction of the gap when compacted during battery production, and the density of the secondary particles becomes easier to increase. Furthermore, when pressure is applied to LiMO during the manufacture of a lithium secondary battery, the cracking direction of the secondary particles tends to become more uniform. As a result, it becomes easier to obtain a lithium secondary battery with high initial discharge capacity and rate characteristics.
[0109] Furthermore, if the average aspect ratio of the voids A is below the aforementioned upper limit, the expansion and contraction of LiMO during charge and discharge is more easily mitigated, and the LiMO crystal structure is more easily stabilized. As a result, it is easier to obtain a lithium secondary battery with high initial discharge capacity and rate characteristics.
[0110] The ratio of the number of secondary particles B to the total number of secondary particles is preferably 3 to 95%, more preferably 5 to 95%, and further preferably 10 to 95%. If the ratio of the number of the above-mentioned secondary particles B is above the lower limit of the above-mentioned range, the expansion and contraction of LiMO caused by the deintercalation and insertion of lithium ions during charging and discharge can be alleviated, and the crystal structure of LiMO is stable. As a result, it becomes easy to obtain a lithium secondary battery with high first discharge capacity and rate characteristics. If the ratio of the number of the above-mentioned secondary particles B is below the upper limit of the above-mentioned range, the energy density is increased by increasing the packing density of the particles, resulting in an improvement in the output characteristics (first discharge capacity and rate characteristics) of the battery.
[0111] The secondary particles B preferably include secondary particles in which the average aspect ratio of voids B in one secondary particle measured by the above-mentioned method is 1.8 to 5.0 (hereinafter also referred to as “secondary particles B′”).
[0112] The ratio of the number of secondary particles B' to the total number of secondary particles is preferably 8% or more, more preferably 10% or more, even more preferably 15% or more, and particularly preferably 20% or more. The ratio of the number of secondary particles B' is preferably 94% or less, more preferably 93% or less, and even more preferably 92% or less. Examples of the ratio of the number of secondary particles B' include 8 to 94%, 10 to 93%, 15 to 92%, and 20 to 92%.
[0113] The average value of the equivalent circle diameter of the voids A is preferably 0.3 μm or more, more preferably 0.4 μm or more. The upper limit of the average value of the equivalent circle diameter of the voids A is not particularly limited as long as the effects of the present invention can be obtained, but is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 5 μm or less.
[0114] Examples of the average value of the circle-equivalent diameter of the voids A include 0.3 to 10 μm, 0.3 to 8 μm, and 0.4 to 5 μm.
[0115] The area-weighted average value of the major diameter of the voids A is preferably 0.2 μm or more, more preferably 0.3 μm or more. The area-weighted average value of the major diameter of the voids A is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 5.0 μm or less. Examples of the area-weighted average value of the major diameter of the voids A include 0.2 to 15 μm, 0.2 to 10 μm, or 0.3 to 5.0 μm.
[0116] The area-weighted average value of the minor diameter of voids A is preferably 0.1 μm or more. The area-weighted average value of the minor diameter of voids A is preferably 3.0 μm or less, more preferably 2.5 μm or less, and even more preferably 2.0 μm or less. Examples of the area-weighted average value of the minor diameter of voids A include 0.1 to 3.0 μm, 0.1 to 2.5 μm, or 0.1 to 2.0 μm.
[0117] The voids possessed by the secondary particles A include three types: voids having an aspect ratio of less than 1.8 (hereinafter also referred to as "voids A1"), voids having an aspect ratio of 1.8 to 5.0 (hereinafter also referred to as "voids A2"), and voids having an aspect ratio exceeding 5.0 (hereinafter also referred to as "voids A3").
[0118] The ratio of the number of voids A2 to the total number of voids A1 to A3 is preferably 20% or greater, more preferably 30% or greater, and even more preferably 40% or greater. The ratio of the number of voids A2 is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less. Examples of the ratio of the number of voids A2 include 20 to 90%, 30 to 80%, and 40 to 70%.
[0119] The ratio of the number of voids A1 to the total number of voids A1 to A3 is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. The ratio of the number of voids A1 is preferably 80% or less, more preferably 70% or less, and even more preferably 60% or less. Examples of the ratio of the number of voids A1 include 10 to 80%, 20 to 70%, or 30 to 60%.
[0120] The ratio of the number of voids A3 to the total number of voids A1 to A3 is preferably 0% or greater, more preferably 0.3% or greater, and even more preferably 1% or greater. The ratio of the number of voids A3 is preferably 40% or less, more preferably 30% or less, and even more preferably 20% or less. Examples of the ratio of the number of voids A3 include 0 to 40%, 0.3 to 30%, or 1 to 20%.
[0121] The number of voids A2 can be obtained by calculating the aspect ratios of all voids for the contours of the void cross-section A identified in the binarized image, and calculating the total number of voids with aspect ratios between 1.8 and 5.0. The number of voids A1 and A3 can also be obtained in the same way.
[0122] The area-weighted average value of the aspect ratio of the secondary particles A is preferably 1.0 or greater. The area-weighted average value of the aspect ratio of the secondary particles A is preferably 5.0 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. Examples of the area-weighted average value of the aspect ratio of the secondary particles A include 1.0 to 5.0, 1.0 to 3.0, and 1.0 to 2.5.
[0123] The area-weighted average value of the major diameter of the secondary particles A is preferably greater than 6.0 μm. The area-weighted average value of the major diameter of the secondary particles A is preferably 20 μm or less, more preferably 17 μm or less, and even more preferably 14 μm or less. Examples of the area-weighted average value of the major diameter of the secondary particles A include greater than 6.0 μm and less than 20 μm, greater than 6.0 μm and less than 17 μm, or greater than 6.0 μm and less than 14 μm.
[0124] The area-weighted average value of the minor diameter of the secondary particles A is preferably 1 μm or greater, more preferably 2 μm or greater, and even more preferably 4 μm or greater. The area-weighted average value of the minor diameter of the secondary particles A is preferably 20 μm or less, more preferably 16 μm or less, and even more preferably 12 μm or less. Examples of the area-weighted average value of the minor diameter of the secondary particles A include 1 to 20 μm, 2 to 16 μm, and 4 to 12 μm.
[0125] The ratio of the area-weighted average of the major diameter of the voids A to the area-weighted average of the major diameter of the secondary particles A is preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more. The ratio of the area-weighted average of the major diameter of the voids A is preferably 0.9 or less, more preferably 0.8 or less, and even more preferably 0.7 or less. Examples of the ratio of the area-weighted average of the major diameter of the voids A include 0.001 to 0.9, 0.005 to 0.8, or 0.01 to 0.7.
[0126] The ratio of the area-weighted average of the minor diameters of the voids A to the area-weighted average of the minor diameters of the secondary particles A is preferably 0.01 or greater, more preferably 0.02 or greater. The ratio of the area-weighted average of the minor diameters of the voids A is preferably 0.5 or less, more preferably 0.3 or less, and even more preferably 0.2 or less. Examples of the ratio of the area-weighted average of the minor diameters of the voids A include 0.01 to 0.5, 0.01 to 0.3, or 0.02 to 0.2.
[0127] If at least one of the ratio of the number of the above-mentioned secondary particles B', the average value of the equivalent circular diameter of the voids A, the area-weighted average value of the major or minor diameter of the voids A, the ratio of the number of voids A1, A2 or A3, the area-weighted average value of the aspect ratio of the secondary particles A, the area-weighted average value of the major and minor diameters of the secondary particles A, the ratio of the area-weighted average value of the major diameter of the voids A to the area-weighted average value of the major diameter of the secondary particles A, and the ratio of the area-weighted average value of the minor diameter of the voids A to the area-weighted average value of the minor diameter of the secondary particles A is greater than the above-mentioned lower limit, the expansion and contraction of LiMO caused by the intercalation and deintercalation of lithium ions during charge and the intercalation of lithium ions during discharge can be alleviated, and the crystal structure of LiMO is stabilized. As a result, it becomes easy to obtain a lithium secondary battery with high initial discharge capacity and rate characteristics. If at least one of the ratio of the number of the above-mentioned secondary particles B', the average value of the equivalent circular diameter of the voids A, the area-weighted average value of the major or minor diameter of the voids A, the ratio of the number of voids A1, A2 or A3, the area-weighted average value of the aspect ratio of the secondary particles A, the area-weighted average value of the major and minor diameters of the secondary particles A, the ratio of the area-weighted average value of the major diameter of the voids A to the area-weighted average value of the major diameter of the secondary particles A, and the ratio of the area-weighted average value of the minor diameter of the voids A to the area-weighted average value of the minor diameter of the secondary particles A is below the above-mentioned upper limit value, the filling density of the particles is increased, thereby increasing the energy density, resulting in improved output characteristics (first discharge capacity and rate characteristics) of the battery.
[0128] LiMO's D 50 It is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 9 μm or more. 50 It is preferably 20 μm or less, more preferably 18 μm or less, and further preferably 9 μm or less. 50 , for example, 5 to 20 μm, 7 to 18 μm, or 9 to 16 μm. 50 If the value is greater than the lower limit, gaps between particles can be formed, and the electrolyte can penetrate into the interior through the gaps, resulting in suppression of internal resistance and improvement of battery characteristics (initial discharge capacity and rate characteristics). 50When the value is below the upper limit of the above range, the size of the gaps between the particles can be suppressed to a certain extent, the particle packing density is increased, and thus the energy density is increased, resulting in improved output characteristics of the battery (initial discharge capacity and rate characteristics).
[0129] LiMO preferably has a layered structure. The crystal structure of LiMO is more preferably a hexagonal crystal structure or a monoclinic crystal structure, and is further preferably a layered rock salt structure.
[0130] The hexagonal crystal structure belongs to a group selected from P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P Any space group in the group consisting of 62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mm, P6 / mcc, P63 / mcm and P63 / mmc.
[0131] In addition, the monoclinic crystal structure belongs to any space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c and C2 / c.
[0132] Among them, in order to obtain a lithium secondary battery with a high initial discharge capacity, the crystal structure is particularly preferably a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to C2 / m.
[0133] In the XRD pattern, the peak area of the diffraction peak existing in the range of 2θ=18.5±1° is set as I D The peak area of the diffraction peak existing in the range of 2θ=44.5±1° is set as I E When I D / I E It is preferably 0.8 or greater, more preferably 0.9 or greater, and even more preferably 1.0 or greater.
[0134] I D / I E It may be 1.4 or less, 1.3 or less, or 1.2 or less.
[0135] As ID / I E , for example, 0.8 to 1.4, 0.9 to 1.3, or 1.0 to 1.2 can be cited.
[0136] <Composition>
[0137] LiMO contains Li. LiMO preferably contains Ni. LiMO may further contain at least one element selected from the group consisting of Co and Mn, may contain at least one element M1 selected from the group consisting of Co, Mn and Al, and may contain one or more elements M2 selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, B, Si, S and P.
[0138] The molar ratio of Co contained in LiMO to the total molar ratio of elements other than Li and oxygen (eg, Ni, M1 and M2 described below) is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less.
[0139] The molar ratio of Co may be 0%, 0.01% or more, or 0.1% or more.
[0140] Examples of the molar ratio of Co include 0 to 5%, 0 to 3%, 0 to 1%, 0.01 to 3%, and 0.1 to 1%.
[0141] Even when the molar number of Co in the LiMO is within the above range, a lithium secondary battery having high initial discharge capacity and rate characteristics can be obtained.
[0142] Composition
[0143] LiMO is preferably represented by the following composition formula (I).
[0144] Li[Li x (Ni (1-y-z) M1 y M2 z ) 1-x ]O2(I)
[0145] In the above composition formula (I), M1 represents one or more elements selected from the group consisting of Co, Mn and Al, M2 represents one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, B, Si, S and P, and the above composition formula (I) satisfies -0.1≤x≤0.2, 0<y<1, 0≤z≤0.2, and y+z<1.
[0146] From the perspective of obtaining a lithium secondary battery with high cycle characteristics, x is preferably -0.05 or greater, more preferably 0 or greater. From the perspective of obtaining a lithium secondary battery with higher initial coulombic efficiency, x is preferably 0.15 or less, more preferably 0.1 or less.
[0147] Examples of x include -0.05 to 0.15, 0 to 0.15, and 0 to 0.1.
[0148] From the perspective of obtaining a lithium secondary battery with high output characteristics (initial discharge capacity and rate characteristics), y is preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more. From the perspective of obtaining a lithium secondary battery with high thermal stability, y is preferably 0.5 or less, and more preferably 0.3 or less.
[0149] Examples of y include 0.001 or more and less than 1, 0.005 to 0.5, and 0.01 to 0.3.
[0150] When LiMO contains the element M2, from the perspective of obtaining a lithium secondary battery with high cycle characteristics, z is preferably 0.001 or greater, more preferably 0.005 or greater. From the perspective of obtaining a lithium secondary battery with high storage characteristics at high temperatures (e.g., 60°C), z is preferably 0.08 or less, more preferably 0.07 or less, and even more preferably 0.05 or less.
[0151] Examples of z include 0.001 to 0.08, 0.005 to 0.07, and 0.005 to 0.05.
[0152] From the viewpoint of obtaining a lithium secondary battery with high thermal stability, the element M2 is more preferably one or more elements selected from the group consisting of Fe, Mg, W, Zr, Nb, B, and Si.
[0153] From the perspective of obtaining a lithium secondary battery with high output characteristics (initial discharge capacity and rate characteristics), y+z is preferably 0.001 or more, more preferably 0.005 or more, and further preferably 0.01 or more. From the perspective of obtaining a lithium secondary battery with high thermal stability, y+z is preferably 0.5 or less, more preferably 0.3 or less, and further preferably 0.1 or less.
[0154] Examples of y+z include 0.001 or more and less than 1, 0.005 to 0.5, 0.01 to 0.3, and 0.01 to 0.1.
[0155] LiMO Manufacturing Method
[0156] The method for manufacturing LiMO includes an MCC manufacturing process for manufacturing MCC, a mixing process for mixing the obtained MCC and a lithium compound, and a firing process for firing the obtained mixture in an oxygen-containing atmosphere.
[0157] <MCC manufacturing process>
[0158] MCC is a compound containing Ni and an optional element M1, and may also contain an element M2, and may be any one of a metal composite hydroxide, a metal composite oxide, and a mixture thereof containing metal elements in a molar ratio represented by the following formula (I').
[0159] Ni:M1:M2 = (1 - y - z):y:z (I')
[0160] In the above formula (I'), M1, M2, y, and z are the same as M1, M2, y, and z in the above compositional formula (I).
[0161] The method for manufacturing MCC includes reacting a nickel salt solution, a metal salt solution containing an element M1, a complexing agent, and an alkaline solution. When preparing the metal composite hydroxide, a metal salt solution containing an optional element M2 may also be added. In this case, MCC becomes a metal composite hydroxide. The metal composite hydroxide can be manufactured by an intermittent coprecipitation method or a continuous coprecipitation method.
[0162] Hereinafter, the method for manufacturing MCC containing Ni and an element M1 will be described as an example. Specifically, by the continuous coprecipitation method described in JP-A-2002-201028, a nickel salt solution, a metal salt solution containing an element M1, a complexing agent, and an alkaline solution are reacted to manufacture Ni (1-y) M1 y (OH)2-represented metal composite hydroxide. y is the same as the above compositional formula (I).
[0163] As the nickel salt as the solute of the nickel salt solution, for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0164] As the metal salt of the element M1 as the solute of the metal salt solution containing the element M1, for example, a sulfate, nitrate, chloride, or acetate of the element M1 can be used. For example, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese sulfate, manganese nitrate, manganese chloride, manganese acetate, aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum acetate, etc. can be cited.
[0165] As the metal salt of the element M2 as the solute of the metal salt solution containing the element M2, for example, a sulfate, nitrate, chloride, or acetate of the element M2 can also be used.
[0166] The metal salt is in the same ratio as the above Ni(1-y) M1 y The amount of each metal salt is determined by the molar ratio of Ni and element M1 in the mixed raw material solution containing the metal salts corresponding to (1-y):y in the above composition formula. Water is used as the solvent.
[0167] The complexing agent is a substance that can form a complex with nickel ions and ions of element M1 in an aqueous solution. Examples thereof include ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, or ammonium fluoride, ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine, preferably an ammonium ion donor.
[0168] In the manufacturing process of the metal composite hydroxide, a complexing agent may be used or not. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution comprising the nickel salt solution, the metal salt solution comprising the element M1, and the complexing agent is preferably greater than 0.00 and less than 2.00 in a molar ratio relative to the total number of moles of the metal salt (nickel salt and metal salt of element M1).
[0169] In the coprecipitation method, in order to adjust the pH of the mixed solution, an alkaline solution is added to the mixed solution before the pH of the mixed solution changes from alkaline to neutral. Examples of the alkaline solution include aqueous solutions of alkali metal hydroxides. Examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide.
[0170] Note that the pH value in this specification is defined as the value measured when the temperature of the mixed solution is 40°C. The pH of the mixed solution is measured when the temperature of the mixed solution sampled from the reaction tank reaches 40°C. If the sampled mixed solution is not at 40°C, the pH is measured after the mixed solution is heated or cooled to 40°C.
[0171] When the nickel salt solution, the metal salt solution containing the element M1 and the complexing agent are continuously supplied to the reaction tank, Ni and the element M1 react to generate Ni. (1-y) M1 y (OH)2.
[0172] The reaction temperature is preferably 20 to 80°C, more preferably 30 to 70°C.
[0173] The pH of the mixed liquid in the reaction tank is preferably, for example, 9 to 13, and more preferably 11 to 13.
[0174] If the reaction temperature and pH are within the above ranges, highly crystalline MCC is obtained. Consequently, the LiMO of this embodiment can be obtained through the mixing and calcining steps. In lithium secondary batteries using such LiMO, the expansion and contraction of the LiMO caused by the intercalation and deintercalation of lithium ions during charging and the intercalation of lithium ions during discharge are mitigated, and the crystal structure of the LiMO is stabilized. As a result, it becomes easier to obtain lithium secondary batteries with high initial discharge capacity and rate characteristics.
[0175] The reaction precipitate formed in the reaction vessel is neutralized while being stirred. The time for neutralizing the reaction precipitate is, for example, 1 to 20 hours.
[0176] Stirring is preferably performed while rotating a stirrer having a stirring blade. By stirring, the substances in the reaction tank are appropriately stirred, and the mixing state in the reaction tank is maintained appropriately, thereby making it easier for the reaction conditions adjusted as described above to be reflected in the physical properties of MCC.
[0177] The reaction tank used in the continuous coprecipitation method may be a type of reaction tank that overflows in order to separate the formed reaction precipitate.
[0178] When the metal composite hydroxide is produced by a batch coprecipitation method, examples of the reaction tank include a reaction tank without an overflow pipe and a device having a concentration tank connected to the overflow pipe and having a mechanism for concentrating the overflowed reaction precipitate in the concentration tank and recirculating it to the reaction tank.
[0179] Various gases, for example, inert gases such as nitrogen, argon, and carbon dioxide, oxidizing gases such as air and oxygen, or mixed gases thereof may be supplied into the reaction vessel.
[0180] After the above reaction, the neutralized reaction precipitate is washed with water and then isolated. For isolation, for example, a method is used in which the slurry containing the reaction precipitate (ie, the coprecipitate slurry) is dehydrated by centrifugation, suction filtration, or the like.
[0181] The separated reaction precipitate is washed, dehydrated, dried, and sieved as necessary to obtain a metal composite hydroxide containing Ni and the element M1.
[0182] The reaction precipitate is preferably washed with a washing liquid such as water, weak acid water, or an alkaline washing liquid. In this embodiment, washing with an alkaline washing liquid is preferred, and washing with an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is more preferred. Alternatively, washing with a washing liquid containing elemental sulfur may be used. Examples of washing liquids containing elemental sulfur include aqueous solutions of potassium and sodium sulfates.
[0183] The washing is preferably performed with a washing liquid having a mass 10 times or greater than that of the reaction precipitate. The temperature of the washing liquid used is preferably set to 30° C. or higher. Furthermore, if washing is performed in a batch manner, it is preferably performed two or more times.
[0184] It should be noted that it is preferred that after washing with a solution other than water, further washing with water is performed to prevent compounds derived from the solution from remaining in the reaction precipitate.
[0185] The drying temperature is preferably 80 to 250° C., more preferably 90 to 230° C. The drying time is preferably 0.5 to 24 hours, more preferably 1 to 20 hours. The drying pressure may be normal pressure or reduced pressure.
[0186] When producing a composite oxide as an MCC metal, it is sufficient to heat the metal composite hydroxide to produce the metal composite oxide. If necessary, multiple heating steps may be implemented. The heating temperature in this specification refers to the set temperature of the heating device. In the case of multiple heating steps, it refers to the temperature of the step in which heating is performed at the highest holding temperature in each heating step.
[0187] The heating temperature is preferably 400 to 700° C., more preferably 450 to 680° C. When the heating temperature is 400 to 700° C., the metal composite hydroxide is sufficiently oxidized, and a metal composite oxide having a BET specific surface area within a suitable range can be obtained.
[0188] The time of holding at the above heating temperature can be 0.1 to 20 hours, preferably 0.5 to 10 hours. The heating rate to the above heating temperature is, for example, 50 to 400°C / hour. In addition, the heating atmosphere can be air, oxygen, nitrogen, argon, or a mixture thereof.
[0189] The heating device may also be provided with a moderate oxygen-containing atmosphere. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and an oxidizing gas, or may be provided with an oxidizing agent in an inert gas atmosphere. By providing a moderate oxygen-containing atmosphere in the heating device, the transition metal contained in the metal composite hydroxide is moderately oxidized, making it easier to control the morphology of the metal composite oxide.
[0190] The oxygen or oxidizing agent in the oxygen-containing atmosphere may contain sufficient oxygen atoms to oxidize the transition metal.
[0191] When the oxygen-containing atmosphere is a mixed gas atmosphere of an inert gas and an oxidizing gas, the atmosphere in the heating device can be controlled by, for example, passing the oxidizing gas through the heating device or bubbling the oxidizing gas into the mixed liquid.
[0192] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, or the like can be used.
[0193] Through the above steps, MCC can be produced. By adjusting the composition of MCC and the amount of the lithium compound described later, D / I E Adjust to the range of this embodiment.
[0194] [Mixing process]
[0195] The MCC produced in the above-mentioned MCC production step is mixed with a lithium compound.
[0196] The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride. Of these, lithium hydroxide, lithium hydroxide hydrate, and lithium carbonate, or a mixture thereof, is preferred.
[0197] MCC and a lithium compound are mixed to obtain a mixture of the lithium compound and MCC, taking into account the composition ratio of the final target product. The amount of Li relative to the total amount (molar ratio) of elements other than oxygen (e.g., Ni, element M1, and element M2) contained in MCC is preferably 0.98 to 1.20, more preferably 0.99 to 1.15, and even more preferably 1.00 to 1.10.
[0198] When mixing MCC with a lithium compound, it is preferable to add and mix the lithium compound separately with the entire amount of MCC, or to add and mix MCC separately with the entire amount of the lithium compound. For example, when adding and mixing the lithium compound with the entire amount of MCC in two divided portions, a portion of the lithium compound is added and mixed with the entire amount of MCC, and the remaining lithium compound is added and mixed with the resulting mixture. For example, when adding and mixing MCC with the entire amount of the lithium compound in two divided portions, a portion of the MCC is added and mixed with the entire amount of the lithium compound, and the remaining MCC is added and mixed with the resulting mixture.
[0199] By adding and mixing the lithium compound separately with the entire amount of MCC, or adding and mixing the MCC separately with the entire amount of lithium compound, Li can be uniformly dispersed throughout the MCC without any imbalance. As a result, LiMO can be produced in which the area-weighted average aspect ratio of the voids A falls within the range of this embodiment and contains secondary particles B at the ratios of this embodiment.
[0200] The number of divisions is preferably 2 to 8 times, more preferably 2 to 6 times.
[0201] When the lithium compound is added and mixed with the entire amount of MCC in separate steps, the amount of the lithium compound added each time can be appropriately set according to the number of separate steps. The amount of the lithium compound added each time is preferably 20 to 50%, and more preferably 30 to 50%, of the total amount of the lithium compound added in this mixing step.
[0202] When MCC is added and mixed with the total amount of the lithium compound in separate portions, the amount of MCC added each time can be appropriately set depending on the number of separate portions. The amount of MCC added each time is preferably, for example, 20 to 50% of the total amount of MCC added in this mixing step, and more preferably 30 to 50%.
[0203] By adjusting the number of separations, the amount of lithium compound added each time, etc., the area-weighted average of the aspect ratio of voids A or secondary particles A, the ratio of the number of secondary particles B or secondary particles B', the average value of the equivalent circular diameter of voids A, the area-weighted average of the major or minor diameter of voids A or secondary particles A, and the ratio of the number of voids A1 to A3 can be set to the range of this embodiment.
[0204] The mixing is preferably performed using, for example, a ball mill, a vibration mill, a mixer, a homogenizer, etc., and the mixing time per time is preferably 1 minute to 20 hours, more preferably 3 minutes to 12 hours.
[0205] By adding and mixing the lithium compound separately into MCC, the area-weighted average value of the aspect ratio of the voids A tends to fall within the above-mentioned range.
[0206] [Firing process]
[0207] The obtained mixture is fired in an oxygen-containing atmosphere. By firing the mixture, LiMO crystals grow.
[0208] The firing temperature in this specification refers to the temperature of the atmosphere in the firing apparatus and is the maximum temperature of the holding temperature (maximum holding temperature).
[0209] When the firing step has a plurality of firing stages, the firing temperature refers to the temperature at the time of firing at the highest holding temperature in each firing stage.
[0210] The calcination temperature is preferably 500-1000°C, more preferably 600-900°C, even more preferably 650-850°C, and particularly preferably 650-820°C. When the calcination temperature is at least the lower limit of the above range, LiMO with a strong crystal structure can be obtained. Furthermore, when the calcination temperature is at most the upper limit of the above range, the volatilization of lithium ions from the surface of the LiMO particles can be reduced.
[0211] The holding time in the firing process is preferably 1 to 50 hours, more preferably 2 to 20 hours. If the holding time in the firing process is below the upper limit of the above range, the volatilization of lithium ions can be suppressed, thereby suppressing the reduction in battery performance. If the holding time in the firing process is above the lower limit of the above range, the development of crystals can be promoted, thereby suppressing the reduction in battery performance.
[0212] In the calcining step, the temperature rise rate until the maximum holding temperature is reached is preferably 80°C / hour or higher, more preferably 100°C / hour or higher, and even more preferably 150°C / hour or higher. The temperature rise rate until the maximum holding temperature is reached is calculated from the time from the start of temperature rise in the calcining apparatus until the holding temperature is reached.
[0213] The firing process preferably includes multiple firing stages with different firing temperatures. For example, it preferably includes a first firing stage and a second firing stage that is fired at a higher temperature than the first firing stage. It may also include firing stages with different firing temperatures and firing times.
[0214] As the firing atmosphere, air, oxygen, nitrogen, argon, or a mixed gas thereof is used depending on the desired composition.
[0215] The mixture of MCC and a lithium compound can also be calcined in the presence of an inactive fluxing agent. The inactive fluxing agent can be added to an extent that does not impair the initial capacity of a battery using the resulting LiMO as a CAM, and can remain in the calcined product. Examples of the inactive fluxing agent include those described in WO2019 / 177032A1.
[0216] The firing apparatus used during firing is not particularly limited, and for example, a continuous firing furnace or a fluidized firing furnace may be used. Examples of the continuous firing furnace include a tunnel furnace and a roller hearth furnace. As the fluidized firing furnace, a rotary kiln may also be used.
[0217] [Optional process]
[0218] (Washing process)
[0219] The calcined product after calcination may be washed with a washing liquid such as pure water or an alkaline washing liquid.
[0220] In the washing step, methods for bringing the washing liquid into contact with the burned material include a method of adding the burned material to each washing liquid and stirring it, a method of applying each washing liquid to the burned material as spray water, etc. Methods for applying each washing liquid to the burned material include a method of adding the burned material to the washing liquid and stirring it, and then separating the burned material from the washing liquid.
[0221] The temperature of the washing liquid is preferably 20° C. or lower, more preferably 15° C. or lower, and even more preferably 10° C. or lower. By controlling the temperature of the washing liquid to a temperature below the upper limit and at which the washing liquid does not freeze, excessive dissolution of lithium ions from the crystal structure of the burned product into the washing liquid during washing can be suppressed.
[0222] It is preferred to wash with a washing liquid having a mass twice or more of the mass of the burned product. Furthermore, if washing is performed in batches, it is preferred to perform the washing twice or more.
[0223] It should be noted that it is preferred that after washing with a solution other than water, further washing with water is performed to prevent the compound derived from the solution from remaining in the reaction precipitate.
[0224] The drying temperature is preferably 80 to 250° C., more preferably 90 to 230° C. The drying time is preferably 0.5 to 24 hours, more preferably 1 to 10 hours. The drying pressure may be normal pressure or reduced pressure.
[0225] LiMO is obtained by the above-described production method.
[0226] <Lithium Secondary Battery>
[0227] A preferred positive electrode for a lithium secondary battery when using the above-mentioned LiMO as CAM will be described. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode.
[0228] Next, a lithium secondary battery which is preferable as a positive electrode will be described.
[0229] An example of a preferred lithium secondary battery using the above-mentioned LiMO as the CAM includes a positive electrode and a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0230] Figure 2 Schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0231] First, if Figure 2 As shown in the partially enlarged view, an electrode group 4 is made by stacking and winding a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 with a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 with a negative electrode lead 31 at one end in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3.
[0232] As an example, the positive electrode 2 includes a positive electrode active material layer 2a containing CAM and a positive electrode current collector 2b having the positive electrode active material layer 2a formed on one surface. Such a positive electrode 2 can be manufactured by the following method: first, a positive electrode mixture containing CAM, a conductive material, and a binder is prepared, and the positive electrode mixture is supported on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0233] As an example, the negative electrode 3 includes an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode composed solely of a negative electrode active material. The negative electrode 3 can be manufactured by the same method as the positive electrode 2 .
[0234] Next, after housing the electrode assembly 4 and an insulator (not shown) in the battery can 5, the bottom of the can is sealed, and the electrolyte 6 is impregnated into the electrode assembly 4, with the electrolyte being disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the top of the battery can 5 is sealed with a top insulator 7 and a sealing member 8, thereby producing a lithium secondary battery 10.
[0235] Examples of the shape of the electrode group 4 include a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicularly to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0236] The shape of the lithium secondary battery having the electrode group 4 may be any of the shapes specified in IEC 60086 or JIS C 8500, which are battery standards specified by the International Electrotechnical Commission (IEC). Examples of such shapes include cylindrical and square shapes.
[0237] Furthermore, lithium secondary batteries are not limited to the aforementioned wound-type configurations, but may also be stacked structures in which a positive electrode, a separator, a negative electrode, and a separator are repeatedly stacked. Examples of stacked lithium secondary batteries include coin-type batteries, button-type batteries, and paper-type (or sheet-type) batteries.
[0238] For the positive electrode, separator, negative electrode, and electrolyte solution constituting the lithium secondary battery, for example, the structures, materials, and production methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0239] <All-solid-state lithium secondary battery>
[0240] The above-mentioned LiMO can be used as CAM of an all-solid-state lithium secondary battery.
[0241] Figure 3 This is a schematic diagram showing an example of an all-solid-state lithium secondary battery. Figure 3The all-solid-state lithium secondary battery 1000 shown in FIG. 1 includes a stack 100 comprising a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130; and an outer casing 200 housing the stack 100. Alternatively, the all-solid-state lithium secondary battery 1000 may have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. Specific examples of bipolar structures include those described in JP-A-2004-95400.
[0242] The positive electrode 110 includes a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 includes the aforementioned CAM and a solid electrolyte. Furthermore, the positive electrode active material layer 111 may also include a conductive material and a binder.
[0243] The negative electrode 120 includes a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. Alternatively, the negative electrode active material layer 121 may contain a solid electrolyte and a conductive material.
[0244] The laminate 100 may include an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may include a separator between the positive electrode 110 and the negative electrode 120.
[0245] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the stacked body 100 from the outer casing 200 , and a sealant (not shown) that seals the opening 200 a of the outer casing 200 .
[0246] The outer package 200 may be formed from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel. Alternatively, the outer package 200 may be formed from a laminate film having at least one surface subjected to corrosion-resistant treatment and formed into a bag.
[0247] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin shape, a button shape, a paper shape (or a sheet shape), a cylindrical shape, a square shape, and a laminated shape (pouch shape).
[0248] As an example, the all-solid-state lithium secondary battery 1000 is shown as having a single stack 100, but the present embodiment is not limited thereto. The all-solid-state lithium secondary battery 1000 may also be configured such that the stack 100 serves as a unit cell and a plurality of unit cells (stacks 100) are enclosed within an outer casing 200.
[0249] For an all-solid-state lithium secondary battery, for example, the structure, materials, and manufacturing method described in
[0141] to
[0181] of WO2022 / 113904A1 can be used.
[0250] Example
[0251] Hereinafter, the present invention will be further described in detail by way of examples, but the present invention is not limited thereto.
[0252] <Measurement of various parameters>
[0253] The measurement of various parameters of LiMO manufactured by the method described later is carried out by the measurement methods described in the above <area-weighted average of the aspect ratio of the voids, etc.>, <D 50 >, <composition> and <XRD pattern>.
[0254] <Measurement of initial discharge capacity and rate characteristics>
[0255] The initial discharge capacity and rate characteristics of the lithium secondary battery are carried out by the measurement methods described in the above <initial discharge capacity and rate characteristics>. When the initial discharge capacity exceeds 200 mAh / g, it is evaluated as having a high initial discharge capacity. When the rate characteristics exceed 50 mAh / g, it is evaluated as having high rate characteristics.
[0256] [Example 1]
[0257] After adding water into a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 70 °C (reaction temperature).
[0258] An aqueous nickel sulfate solution, an aqueous manganese sulfate solution and an aqueous aluminum sulfate solution were mixed so that the molar ratio of Ni:Mn:Al became 93:3.5:3.5 to prepare a mixed raw material liquid 1. [[ID=二十九]]
[0259] Under a nitrogen flow, the mixed raw material liquid 1 and an aqueous ammonium sulfate solution as a complexing agent were continuously added to the reaction tank while stirring. An aqueous sodium hydroxide solution was added dropwise as appropriate so that the pH of the mixed liquid in the reaction tank became 12 (measurement temperature: 40 °C) to obtain a reaction precipitate 1.
[0260] Relative to the mass of the reaction precipitate 1, an aqueous sodium hydroxide solution with 20 times the mass (sodium hydroxide concentration: 5% by mass) was used for washing the reaction precipitate 1. After washing, dehydration was carried out with a centrifuge, and further washing and dehydration with water were carried out, and drying was carried out at 105 °C for 20 hours, thereby obtaining a metal composite hydroxide containing Ni, Mn and Al. By heating the metal composite hydroxide at 650 °C for 5 hours, MCC1 as a metal composite oxide was obtained.
[0261] Lithium hydroxide monohydrate was weighed so that the amount of Li relative to the total amount of Ni, Mn, and Al contained in MCC1 (molar ratio) was 1.04. Half of the weighed amount of lithium hydroxide monohydrate was added to MCC1 and mixed for 5 minutes to obtain Mixture 1A. The remaining half of the lithium hydroxide monohydrate was then added to Mixture 1A and mixed for a further 5 minutes to obtain Mixture 1.
[0262] Next, the resulting mixture 1 was calcined at 650°C (heating rate: 300°C / hour) for 5 hours in an oxygen atmosphere, and then calcined at 750°C (heating rate: 300°C / hour) for 5 hours to obtain powder 1. The resulting powder 1 was mixed with pure water adjusted to a temperature of 5°C so that the mass ratio of the powder 1 to the total mass was 0.3 to prepare a slurry. After stirring the slurry for 20 minutes, it was dehydrated and further rinsed with pure water adjusted to a temperature of 5°C in an amount twice the mass of the powder 1, isolated, and dried at 150°C to obtain LiMO1. In the above composition formula (I), LiMO1 has x = 0.04, y = 0.07, and z = 0.00, and the elements M1 are Mn and Al.
[0263] Various parameters of LiMO1 are shown in Table 1 (hereinafter, the same applies to Examples 2 to 5 and Comparative Examples 1 to 3).
[0264] A lithium secondary battery was produced using the obtained LiMO1 as CAM, and the initial discharge capacity and rate characteristics were measured. The results are shown in Table 1 (the same applies to Examples 2 to 5 and Comparative Examples 1 to 3 below).
[0265] [Example 2]
[0266] LiMO2 was obtained by following the same procedures as in Example 1, except that the pH of the solution in the reaction tank was set to 11.4 (measurement temperature: 40°C) and lithium hydroxide monohydrate was weighed so that the amount of Li relative to the total amount of Ni, Mn, and Al contained in MCC1 (molar ratio) was 1.02. In the above composition formula (I), x=0.02, y=0.07, and z=0.00 are represented by LiMO2, and the elements M1 are Mn and Al.
[0267] [Example 3]
[0268] MCC3, a metal composite oxide, was obtained by the same procedures as in Example 1, except that the molar ratio of Ni:Mn:Al was set to 93:1:6 and the pH of the solution in the reaction vessel was set to 11.4 (measurement temperature: 40°C). LiMO3 was obtained by the same procedures as in Example 1, except that lithium hydroxide monohydrate was weighed so that the amount of Li was 1.03 relative to the total amount of Ni, Mn, and Al contained in MCC3 (molar ratio). In the above composition formula (I), x = 0.03, y = 0.07, and z = 0.00, and the elements M1 are Mn and Al.
[0269] [Example 4]
[0270] MCC4, a metal composite oxide, was obtained by the same procedures as in Example 1, except that an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, an aqueous manganese sulfate solution, and an aqueous aluminum sulfate solution were mixed so that the molar ratio of Ni:Co:Mn:Al was 92.9:0.1:3.5:3.5. LiMO4 was obtained by the same procedures as in Example 1, except that lithium hydroxide monohydrate was weighed so that the amount of Li was 1.03 relative to the total molar ratio of Ni, Co, Mn, and Al contained in MCC4. In the above composition formula (I), x = 0.03, y = 0.08, and z = 0.00, and the elements M1 are Co, Mn, and Al. The molar ratio of Co contained in LiMO4 to the total molar ratio of elements other than Li and oxygen was 1%.
[0271] [Example 5]
[0272] Lithium hydroxide monohydrate was weighed so that the amount of Li relative to the total amount of Ni, Mn, and Al contained in MCC1 (molar ratio) was 1.05. The same procedures as in Example 1 were followed to obtain LiMO5. In the above composition formula (I), x = 0.05, y = 0.07, and z = 0.00, and the elements M1 are Mn and Al.
[0273] [Comparative Example 1]
[0274] After water was added to a reaction vessel equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 70° C. (reaction temperature).
[0275] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, and an aluminum sulfate aqueous solution were mixed so that the molar ratio of Ni:Co:Al became 88:9:3 to prepare a mixed raw material solution 6 .
[0276] Under nitrogen flow, the mixed raw material solution 6 and an aqueous ammonium sulfate solution as a complexing agent were continuously added to the reaction vessel with stirring. A sodium hydroxide solution was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel reached 11.4 (measurement temperature: 40°C) to obtain a reaction precipitate 6.
[0277] The reaction precipitate 6 was washed with a sodium hydroxide aqueous solution (sodium hydroxide concentration: 5% by mass) 20 times the mass of the reaction precipitate 6. After washing, the precipitate was dehydrated using a centrifuge, washed with water, dehydrated, and dried at 105°C for 20 hours to obtain a metal composite hydroxide containing Ni, Co, and Al. The metal composite hydroxide was heated at 650°C for 5 hours to obtain MCC6, a metal composite oxide.
[0278] Lithium hydroxide monohydrate was weighed so that the amount of Li was 1.03 (molar ratio) relative to the total amount of Ni, Co, and Al contained in MCC 6. The entire amount of the weighed lithium hydroxide monohydrate was added to MCC 6 and mixed for 5 minutes to obtain a mixture 6.
[0279] Next, the obtained mixture 6 was calcined at 650°C (heating rate: 300°C / hour) for 5 hours in an oxygen atmosphere, and then calcined at 740°C (heating rate: 300°C / hour) for 5 hours to obtain powder 6. The obtained powder 6 was mixed with pure water adjusted to a liquid temperature of 5°C so that the mass ratio of the above-mentioned powder 6 to the total amount was 0.3 to prepare a slurry. After stirring the slurry for 20 minutes, it was dehydrated and further rinsed with pure water adjusted to a liquid temperature of 5°C in an amount twice the mass of the above-mentioned powder 6. After separation, it was dried at 150°C to obtain LiMO6. In the above-mentioned composition formula (I), LiMO6 has x=0.03, y=0.12, and z=0.00, and the elements M1 are Co and Al. The ratio of the number of moles of Co contained in LiMO6 to the total number of moles of elements other than Li and oxygen is 9%.
[0280] [Comparative Example 2]
[0281] Lithium hydroxide monohydrate was weighed so that the amount of Li relative to the total amount of Ni, Mn, and Al contained in MCC1 (molar ratio) was 1.03, and the entire amount of the weighed lithium hydroxide monohydrate was added to MCC1 and mixed for 5 minutes. The same procedures as in Example 1 were followed to obtain LiMO7. In the above composition formula (I), x = 0.03, y = 0.07, and z = 0.00 are represented, and the elements M1 are Mn and Al.
[0282] [Comparative Example 3]
[0283] MCC8, a metal composite oxide, was obtained by the same procedures as in Example 1, except that an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution were mixed so that the molar ratio of Ni:Co:Mn was 34:36:30. LiMO8 was obtained by the same procedures as in Comparative Example 1, except that lithium hydroxide monohydrate was weighed so that the amount of Li was 1.03 relative to the total amount (molar ratio) of Ni, Mn, and Co contained in MCC8. In the above composition formula (I), x = 0.03, y = 0.66, and z = 0.00, and the elements M1 are Mn and Co. The molar ratio of Co contained in LiMO8 to the total molar ratio of elements other than Li and oxygen was 34%.
[0284] It should be noted that the majority of LiMO8 consists of secondary particles with an equivalent circle diameter of 6.0 μm or less. Removing these particles would not yield a sufficient number of particles for the measurement method described in "Area-weighted average of aspect ratio of voids, etc." Therefore, the image calculation function was used to remove secondary particles with an equivalent circle diameter of 1.5 μm or less from the binarized image, replacing those with an equivalent circle diameter of 6.0 μm or less. The measurement was performed in the same manner, except that these particles were removed using the image calculation function.
[0285]
[0286] The lithium secondary batteries produced using the LiMO of Examples 1 to 5 as CAM, in which the area-weighted average aspect ratio of the voids A was 1.8 to 5.0 and the proportion of the number of secondary particles B was 3 to 95%, showed improved initial discharge capacity and rate characteristics.
[0287] Description of Reference Numerals
[0288] 1: Separator, 2: Positive electrode, 2a: Positive electrode active material layer, 2b: Positive electrode collector, 3: Negative electrode, 4: Electrode group, 5: Battery can, 6: Electrolyte, 7: Top insulator, 8: Sealing member, 10: Lithium secondary battery, 21: Positive electrode lead, 31: Negative electrode lead, 40: Cross section of secondary particle, 41, 42, 43: Solid cross section of secondary particle, 44, 45: Void cross section, 100: Laminated body, 110: Positive electrode, 111: Positive electrode active material layer, 112: Positive electrode collector, 113: External terminal, 120: Negative electrode, 121: Negative electrode active material layer, 122: Negative electrode collector, 123: External terminal, 130: Solid electrolyte layer, 200: Outer packaging, 200a: Opening, 1000: All-solid-state lithium secondary battery
Claims
1. A lithium metal composite oxide comprising a plurality of secondary particles, wherein the secondary particles are aggregates of primary particles. At least a portion of the secondary particles has voids inside. Regarding the contour shape of the voids exposed in the cross section of the secondary particle having the voids therein, the area-weighted average of the aspect ratios of the voids having an equivalent circle diameter of 0.2 μm or more is 1.8 or more and 5.0 or less, The ratio of the number of secondary particles having voids with an equivalent circle diameter of 0.5 μm or more in the interior to the total number of the secondary particles is 3% or more and 95% or less.
2. The lithium metal composite oxide according to claim 1, wherein The average value of the equivalent circle diameter of the voids having an equivalent circle diameter of 0.2 μm or more is 0.3 μm or more.
3. The lithium metal composite oxide according to claim 1 or 2, wherein The area-weighted average value of the major axes of the voids having an equivalent circle diameter of 0.2 μm or greater is 0.2 μm or greater and 15 μm or less.
4. The lithium metal composite oxide according to claim 1 or 2, wherein The area-weighted average of the aspect ratios of the secondary particles having voids having an equivalent circle diameter of 0.2 μm or greater therein is 1.0 or greater and 5.0 or less.
5. The lithium metal composite oxide according to claim 1 or 2, wherein The ratio of the area-weighted average of the major axes of the voids having an equivalent circle diameter of 0.2 μm or greater to the area-weighted average of the major axes of the secondary particles having the voids having an equivalent circle diameter of 0.2 μm or greater therein is 0.001 to 0.
9.
6. The lithium metal composite oxide according to claim 1 or 2, wherein 50% cumulative volume particle size is D 50 It is 5 μm or more and 20 μm or less.
7. The lithium metal composite oxide according to claim 1 or 2, wherein The lithium metal composite oxide contains Li and Ni and may contain at least one element selected from the group consisting of Co and Mn, wherein the ratio of the number of moles of Co contained in the lithium metal composite oxide to the total number of moles of elements other than Li and oxygen is 5% or less.
8. The lithium metal composite oxide according to claim 1 or 2, which is represented by the following composition formula (I): Li[Li x (Nor (1-y-z) M1 y M2 z ) 1-x ]O2(I) In the composition formula (I), M1 represents one or more elements selected from the group consisting of Co, Mn and Al, M2 represents one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, B, Si, S and P, and the composition formula (I) satisfies -0.1≤x≤0.2, 0<y<1, 0≤z≤0.2, and y+z<1.
9. The lithium metal composite oxide according to claim 1 or 2, wherein In the powder X-ray diffraction measurement using CuKα radiation, the peak area of the diffraction peak existing in the range of 2θ=18.5±1° is set as I D The peak area of the diffraction peak existing in the range of 2θ=44.5±1° is set as I E When I D / I E It is above 0.
8. 10 . A positive electrode active material for a lithium secondary battery, comprising the lithium metal composite oxide according to claim 1 . 11 . A positive electrode for a lithium secondary battery, comprising the positive electrode active material for a lithium secondary battery according to claim 10 . 12 . A lithium secondary battery comprising the positive electrode for a lithium secondary battery according to claim 11 .
Citation Information
Patent Citations
High density nickel hydroxide coprecipitated with cobalt and manganese, and method for producing the same
JP2002201028A
Bipolar battery and its control method
JP2004095400A
Nonaqueous electrolyte secondary battery, and cathode active material for nonaqueous electrolyte secondary battery
JP2017004635A
Lithium metal composite oxide powder, positive electrode active substance for lithium secondary battery, positive electrode, and lithium secondary battery
WO2019177032A1
Method for producing lithium metal composite oxide
WO2022113904A1